Green phosphorescent organic light-emitting diode exhibiting highest external quantum efficiency with ultra-thin undoped emission layer - Shin Woo Kang (Nature Portfolio, 2021)
Abstract In this study, we report highly efficient green phosphorescent organic light-emitting diodes (OLEDs) with ultra-thin emission layers (EMLs). We use tris[2-phenylpyridinato-C2,N]iridium(III) (Ir(ppy)3), a green phosphorescent dopant, for creating the OLEDs. Under systematic analysis, the peak external quantum efficiency (EQE) of an optimized device based on the ultra-thin EML structure is found to be approximately 24%. This result is highest EQE among ultra-thin EML OLEDs and comparable to the highest efficiency achieved by OLEDs using Ir(ppy)3 that are fabricated via conventional doping methods. Moreover, this result shows that OLEDs with ultra-thin EML structures can achieve ultra-high efficiency.